2023
DOI: 10.2903/j.efsa.2023.7917
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza overview December 2022 – March 2023

Abstract: Between 3 December 2022 and 1 March 2023 highly pathogenic avian influenza (HPAI) A(H5N1) virus, clade 2.3.4.4b, was reported in Europe in domestic (522) and wild (1,138) birds over 24 countries. An unexpected number of HPAI virus detections in sea birds were observed, mainly in gull species and particularly in black-headed gulls (large mortality events were observed in France, Belgium, the Netherlands, and Italy). The close genetic relationship among viruses collected from black-headed gulls suggests a southw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 38 publications
2
69
0
Order By: Relevance
“…This finding was further confirmed by the phylogenetic analysis performed on the other viral segments, which showed that both strains were closely related to strains circulating in Belgium at that time ( Supplementary Figure 5 ). The whole genome analysis revealed both strains belonged to the AB genotype (H5N1-A/duck/Saratov/29-02/2021-like), the main circulating genotype at that time in Europe [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was further confirmed by the phylogenetic analysis performed on the other viral segments, which showed that both strains were closely related to strains circulating in Belgium at that time ( Supplementary Figure 5 ). The whole genome analysis revealed both strains belonged to the AB genotype (H5N1-A/duck/Saratov/29-02/2021-like), the main circulating genotype at that time in Europe [6].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the occasions on which mammals have been exposed to the virus have become more frequent in turn. Infection generally occurs following exposure to contaminated feces or water, or animal carcasses [6]. Sporadic infections of wild mammals have been described in the past, but have never been as frequent as in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have confirmed the presence of a high number of positive for the HPAIV H5N1 virus, clade 2.3.4.4b, in Europe between 3 December 2022 and 1 March 2023 (EFSA et al, 2023). In Spain, an outbreak of HPAIV between May 2022 and March 2023 was reported, and the Spanish authorities also reported 100 cases in wild birds and one in poultry (WOAH, 2023).…”
Section: Introductionmentioning
confidence: 91%
“…A wide range of birds and a number of mammalian species have been found to be infected with HPAIVs, though mortality rates depend in part on differences in taxa- and species-specific traits (European Food Safety Authority et al 2023a; Teitelbaum et al 2023; Alkie et al 2023). For example, unusual mortality among dabbling ducks has not been largely attributed to HPAIV despite its detection in apparently healthy birds, though some species of diving ducks, such as Tufted Ducks ( Aythya fuligula ), are particularly susceptible to HPAIVs and often exhibit high mortality rates (Keawcharoen et al 2008; Kleyheeg et al 2017; Caliendo et al 2022).…”
Section: Introductionmentioning
confidence: 99%